Exploration of nitric oxide generation from S-nitrosoglutathione for the advancement of anti-fouling glucose biosensor membrane materials - Melvin, Alyssa C., author; Reynolds, Melissa M., advisor; Zadrozny, Joseph, committee member; Farmer, Delphine, committee member; Chen, Thomas, committee member (Colorado State University. Libraries, 2022)
Blood-contacting medical devices such as implantable glucose sensors suffer from biofouling which limits the lifetime of the device and puts the patient at risk of arterial embolism and infection. Researchers have been developing medical device coatings to address the two causes of surface biofouling: thrombus and biofilm formation. One promising strategy is surface-localized production of nitric oxide (NO), a biomolecule with antithrombotic and antibacterial physiological functions, as a multifunctional therapeutic for biofouling prevention. Because NO is a gaseous free radial with a very short physiological half-life, achieving localized NO generation presents a clear challenge. An innovative approach that will be explored herein is incorporating catalysts on the medical device surface that release NO from endogenous NO sources, S-nitrosothiols (RSNOs). A water stable copper-based metal–organic framework (MOF) CuBTTri, Cu(II) benzene-1,3,5-tris(1H-1,2,3-triazoy-5-yl), has been shown to be an effective catalyst for the generation of NO from RSNOs. Two RSNOs, S-nitrosoglutathione (GSNO) and S-nitroso-N-acetylpenicillamine (SNAP), are commonly used in the development of new NO-generating materials. It is known that RSNOs are susceptible to decomposition by stimuli including heat, light, and trace metal ions which can inadvertently be introduced through basic handling, storage conditions, and experimental setups. Despite their frequent use, there is limited and conflicting literature examining the comparative stability of GSNO and SNAP. In order to accurately characterize and quantify the behavior of NO-generating materials, reliable and robust methods must be developed to prevent spontaneous RSNO decomposition under the desired experimental conditions. In Chapter 2, the comparative stability of GSNO and SNAP was thoroughly examined to inform subsequent experiments in the development of CuBTTri-based anti-fouling materials with RSNOs as the NO source. Though CuBTTri is an effective catalyst for this reaction, solid state material must be immobilized into a flexible, processable scaffold for coating devices. In Chapter 3, the effects of incorporating CuBTTri into a medical grade polyurethane composite material on NO generation is explored. In Chapter 4, the effects of three key parameters of CuBTTri composite materials, MOF particle size, MOF loading, and polymer concentration, on NO generation are evaluated to assess the tunability of these next-generation materials. In Chapter 5, the effects of the CuBTTri/polyurethane composite material on the enzyme function and analytical performance of a glucose biosensor are examined. Though metal ion-promoted NO release from RSNOs is promising strategy for the development of NO-generating materials, the majority of studies focus on copper, and few have surveyed the ability of other common metal ions to produce this effect. Finally, in Chapter 6, NO generation from GSNO by Cu2+ and twenty transition and post-transition metal ions was monitored using NO-selective chemiluminescence-based detection to expand the range of potential metals for the development of NO-based anti-fouling materials.
Keywords: biosensors; materials science; nitric oxide; glucose sensors; biocompatible; metal-organic frameworks